Switchable S = 1/2 and J = 1/2 Rashba bands in ferroelectric halide perovskites - Kim, Minsung; Im, Jino; Freeman, Arthur J.; Ihm, Jisoon; Jin, Hosub (Proceedings of the National Academy of Sciences - PNAS, 2014)
The Rashba effect is spin degeneracy lift originated from spin–orbit coupling under inversion symmetry breaking and has been intensively studied for spintronics applications. However, easily implementable methods and corresponding materials for directional controls of Rashba splitting are still lacking. Here, we propose organic–inorganic hybrid metal halide perovskites as 3D Rashba systems driven by bulk ferroelectricity. In these materials, it is shown that the helical direction of the angular momentum texture in the Rashba band can be controlled by external electric fields via ferroelectric switching. Our tight-binding analysis and first-principles calculations indicate that [Formula] and [Formula] Rashba bands directly coupled to ferroelectric polarization emerge at the valence and conduction band edges, respectively. The coexistence of two contrasting Rashba bands having different compositions of the spin and orbital angular momentum is a distinctive feature of these materials. With recent experimental evidence for the ferroelectric response, the halide perovskites will be, to our knowledge, the first practical realization of the ferroelectric-coupled Rashba effect, suggesting novel applications to spintronic devices.